2017
DOI: 10.1245/s10434-017-6273-9
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot Study on the Value of Omentoplasty in Abdominoperineal Resection with Primary Perineal Closure for Rectal Cancer

Abstract: BackgroundPerineal wound complications are often encountered following abdominoperineal resection (APR). Filling of the pelvic space by omentoplasty (OP) might prevent these complications, but there is scant evidence to support its routine application.ObjectiveThe aim of this study was to evaluate the impact of OP on perineal wound complications.MethodsAll patients undergoing APR with primary perineal closure (PPC) for non-locally advanced rectal cancer in 71 Dutch centers in 2011 were selected from a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 13 publications
1
46
1
1
Order By: Relevance
“…The higher perineal hernia rate after OP is in line with previous studies [7,8]. Although a causal relation cannot be confirmed, the hypothesis is that the pedicled omentum will function as a large amount of loose fatty tissue that will easily descend through the pelvic outlet in the absence of a pelvic floor, while a few loops of small bowel are restricted by a certain mesenteric length in the possibility of herniating at the level of the perineum.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The higher perineal hernia rate after OP is in line with previous studies [7,8]. Although a causal relation cannot be confirmed, the hypothesis is that the pedicled omentum will function as a large amount of loose fatty tissue that will easily descend through the pelvic outlet in the absence of a pelvic floor, while a few loops of small bowel are restricted by a certain mesenteric length in the possibility of herniating at the level of the perineum.…”
Section: Discussionsupporting
confidence: 88%
“…It could therefore be that a true effect may not be demonstrated due to relatively low numbers. However, as only few patients would require surgical management, and this study as well as two recent large studies showed no significant reduction in reoperation rate for ileus [7,8], it is questionable whether this potential effect of OP would be clinically relevant.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This was confirmed in a recent review showing a reduction of perineal wound morbidity after APR when an omentoplasty is created [17]. A large cross-sectional study in the Netherlands, however, revealed no reduction of pelvic abscesses after APR with primary closure of the perineal wound and omentoplasty compared to primary closure without omentoplasty [18]. The present survey found that only 19% of respondents never perform an omentoplasty in iAPR, despite conclusive evidence on the additional value and the need for additional dissection and increase in operating time.…”
Section: Discussionmentioning
confidence: 69%